Age variations in judgments of ‘great’ art works - North, Adrian; Hargreaves, David (John Wiley & Sons Ltd., 2002)
This paper reports the results of two large-scale surveys concerning nominations of ‘greatness’ in the arts. In Study 1, 1088 respondents to a national newspaper survey nominated the greatest art works of the past 1000 years. Analyses indicated that there was some, albeit limited, evidence that older respondents nominated older art works, but no evidence of a tendency to nominate works produced during the participants’ adolescence/early adulthood. In Study 2, a very brief questionnaire distributed through a CD retail chain, a national newspaper, and a national TV station asked 12,502 participants to nominate up to three of the greatest pop musicians of all time. Analyses indicated a tendency to nominate musicians who were successful while the participants themselves were in adolescence/early adulthood. These results are discussed in terms of the extent to which age can explain judgments of artistic ‘greatness’ within different art forms.